Stromal coexpression of uPA/PAI-1 protein predicts poor disease outcome in endocrine-treated postmenopausal patients with receptor-positive early breast cancer. (August 2019) - Singer, C.F.; Filipits, M.; Jahn, S.W.; Abete, L.; Jakesz, R.; Greil, R.; Bauernhofer, T.; Kwasny, W.; Seifert, M.; Fitzal, F.; Kastner, M.; Schmitt, M.; et al.
Abstract (198 words): Background: To evaluate whether uPA/PAI-1 protein in hormone receptor–positive (HR+) breast tumor can predict prognosis in early breast cancer (BC). Methods: 606 women with HR + BC who had ≥5 years of endocrine therapy and in whom tumor tissue was available were included in this analysis. Stromal uPA/PAI-1 protein expression was evaluated by immunohistochemistry and correlated with distant recurrence-free survival (DRFS) and overall survival (OS). Results: Stromal uPA was detected in 292/538 tumors (54.3%) while 269/505 samples (53.3%) exhibited stromal PAI-1. Co-expression of both proteins was found in 163/437 (37.3%) samples. Stromal uPA/PAI-1 co-expression was not associated with tumor size, age, nodal status, grading, or receptor status. Tumor stroma with both uPA and PAI-1 protein expression were more likely to have a shorter DRFS (HR: 1.87; 95%CI 1.18–2.96; p = 0.007) and OS (HR: 1.29; 95%CI 0.93–1.80; p = 0.129) than women without uPA/PAI-1 co-expression. After a median follow-up of 10 years, women with uPA/PAI-1-positive tumors experienced a significantly shorter DRFS (86.5% vs 72.4%; p < 0.001) and OS (70.4% vs 58.9%; p = 0.020) compared to women with uPA/PAI-1 negative tumors. Conclusion: Stromal co-expression of uPA and PAI-1 in breast cancer predicts poor DRFS and OS in postmenopausal women with HR + early-stage BC who receive endocrine therapy. Highlights: The first study to evaluate if protein expression of uPA/PAI-1 in FFPE tumor samples. IHC uPA/PAI-1 in FFPE could predict prognosis in early HR + breast cancer. Stromal IHC uPA/PAI-1 predicts poor survival in HR + BC.